Inter-industry and intra-industry switching as sources of productivity growth: Structural change of Finland's ICT industries - Natalia Kuosmanen; Timo Kuosmanen (The Research Institute of the Finnish Economy (ETLA), 2023)
Structural change is an important driver of productivity growth at the aggregate level. While previous productivity decompositions account for the contributions of market entry and exit, they overlook continuing firms that switch from one industry to another. We develop an improved productivity decomposition that accounts for both intra-industry and inter-industry switching, is applicable to both static and inter-temporal settings, and ensures consistent aggregation of firm level productivity to the industry level. The proposed decomposition is applied to Finland's information and communication technology (ICT) industry in the first two decades of the 21st century. This industry experienced major structural changes due to the rapid downfall of Nokia, the world's largest mobile phone manufacturer at the beginning of our study period. Our results reveal that the sharp decline of labor productivity was associated with the structural changes, whereas the surviving firms that continued in the same industry managed to improve their productivity. Our results indicate that industry switching can dampen or enhance the productivity impacts of structural change, especially during the times of crisis and recession.
Keywords: D24; L16; O47; 330; Entry and exit; Labor productivity; Product switching; Reallocation of resources